2014
DOI: 10.1371/journal.pone.0108889
|View full text |Cite|
|
Sign up to set email alerts
|

Tempol, a Superoxide Dismutase Mimetic Agent, Ameliorates Cisplatin-Induced Nephrotoxicity through Alleviation of Mitochondrial Dysfunction in Mice

Abstract: BackgroundMitochondrial dysfunction is a crucial mechanism by which cisplatin, a potent chemotherapeutic agent, causes nephrotoxicity where mitochondrial electron transport complexes are shifted mostly toward imbalanced reactive oxygen species versus energy production. In the present study, the protective role of tempol, a membrane-permeable superoxide dismutase mimetic agent, was evaluated on mitochondrial dysfunction and the subsequent damage induced by cisplatin nephrotoxicity in mice.Methods and FindingsNe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 70 publications
4
43
0
Order By: Relevance
“…Earlier studies in the same experimental model also demonstrated that chronic losartan treatment improved kidney structure [3], while tempol effectively suppressed glomerular and tubular damage in various models of proteinuric nephropathy [1012]. Here, Up/cr ratio showed higher positive correlation with glomerulosclerosis, than with an index of tubular damage, and was also in accordance with the MMP-1 protein expression.…”
Section: Discussionsupporting
confidence: 65%
“…Earlier studies in the same experimental model also demonstrated that chronic losartan treatment improved kidney structure [3], while tempol effectively suppressed glomerular and tubular damage in various models of proteinuric nephropathy [1012]. Here, Up/cr ratio showed higher positive correlation with glomerulosclerosis, than with an index of tubular damage, and was also in accordance with the MMP-1 protein expression.…”
Section: Discussionsupporting
confidence: 65%
“…The effect of co-administration of Tempol with cisplatin on the suppression of tumor growth in mice was similar to that observed in mice treated with cisplatin alone. Therefore, Tempol did not interfere with the anti-cancer effect of cisplatin against the growth of solid carcinomas [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Tempol has been reported to restore the intracellular oxidative balance and reduce oxidative stress, resulting in alleviation of nephrotoxicity in mice [4], and reduced infarct size in rat and rabbit myocardial infarction models [5]. Moreover, it exerts a protective effect against lymphocyte genotoxicity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Protein expression was assessed as previously described by Ahmed et al [30] using primary antibodies against peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) and rho kinase 1 (ROCK1) from GeneTex, Inc. (Irvine, CA, USA) as well as phosphorylated-Akt (p-Akt), endothelial nitric oxide synthase (eNOS), inducible nitric oxide synthase (iNOS), Bax, Bcl-2, and beta-actin (β-actin) from Thermo Fisher Scientific Inc. (Rockford, IL, USA). The amount of protein was quantified by densitometric analysis of the autoradiograms using a scanning laser densitometer (Biomed Instrument Inc., USA).…”
Section: Western Blot Analysismentioning
confidence: 99%